Insight on the Linkage between Foreign Direct Investment and Unemployment: Evidence from Nigerian Data - Sunday Ojo Akinmulegun; Oludayo Elijah Adekunle (Journal of Accounting Research, Organization and Economics, 2022)
The menace of unemployment has continued to pose a great challenge to policy makers, practitioners and scholars in Nigeria. This is in spite of government’s diverse efforts at reducing unemployment. This study gave new insight into the short and long run effects of foreign direct investment on unemployment rate in Nigeria base on time series secondary data covering 1986 to 2018. The novelty of this study lies in using more rigorous technique of Autoregressive Distributed Lag-Bound co-integration approach to give new insight on the nexus between foreign direct investment and unemployment rate. Augmented Dickey–Fuller unit root test, Bound Co-integration test and Autoregressive Distributed Lag techniques were used for analysis. Base on findings, evidence of long run relationship was discovered between foreign direct investment and unemployment rate in Nigeria. The short and long run estimate suggested that foreign direct investment contributed significantly to the reduction of unemployment rate in Nigeria. The implication of these findings is that, foreign direct investment through assets expansion, technology, and knowledge diffusion generate employment opportunities thereby pushing unemployment rate trend downward in the economy.